Perbandingan Pemahaman Konsep Dasar Fisika Antara Siswa yang Berasal dari SMP Induk Perkotaan dan SMP Pedesaan pada Siswa Kelas X IPA SMA Negeri 2 Majene - Sutrisno Sutrisno (Journal on Education, 2022)
The purpose of this study was to determine the students' understanding of the basic concepts of physics from urban junior high schools and rural junior high schools in class x IPA of Majene 2 Public High School, as well as to find out that there was a comparison of understanding of basic physics concepts between students from urban and rural junior high schools in class X IPA SMA Negeri 2 Majene. Determination of the sample through proportional random sampling technique. The data collection instrument in this study was a written instrument. The data analysis technique uses descriptive and inferential analysis, namely the two sample t test. Based on the results of data analysis using descriptive statistics, it was obtained that the average level of understanding of the basic concepts of physics for students from urban primary junior high schools was in the good category and rural junior high school students were in the medium category. While the inferential results are F count ˃ F table so that there is a comparison of understanding of the basic concepts of physics between students from urban primary junior high schools and rural junior high schools in class X IPA students of SMA Negeri 2 Majene